Performance of a knowledge‐based planning model for optimizing intensity‐modulated radiotherapy plans for partial breast irradiation. Issue 3 (22nd December 2021) - Frederick, Amy; Roumeliotis, Michael; Grendarova, Petra; Quirk, Sarah
Abstract: Purpose: To evaluate a knowledge‐based (KB) planning model for RapidPlan, generated using a five‐field intensity‐modulated radiotherapy (IMRT) class solution beam strategy and rigorous dosimetric constraints for accelerated partial breast irradiation (APBI). Materials and methods: The RapidPlan model was configured using 64 APBI treatment plans and validated for 120 APBI patients who were not included in the training dataset. KB plan dosimetry was compared to clinical plan dosimetry, the clinical planning constraints, and the constraints used in phase III APBI trials. Dosimetric differences between clinical and KB plans were evaluated using paired two‐tailed Wilcoxon signed‐rank tests. Results: KB planning was able to produce IMRT‐based APBI plans in a single optimization without manual intervention that are comparable or better than the conventionally optimized, clinical plans. Comparing KB plans to clinical plans, differences in PTV, heart, contralateral breast, and ipsilateral lung dose–volume metrics were not clinically significant. The ipsilateral breast volume receiving at least 50% of the prescription dose was statistically and clinically significantly lower in the KB plans. Conclusion: KB planning for IMRT‐based APBI provides equivalent or better dosimetry compared to conventional inverse planning. This model may be reliably applied in clinical practice and could be used to transfer planning expertise to ensure consistency in APBI plan quality.